SISTEM INFORMASI MONITORING KESEHATAN IBU HAMIL PADA 3 FASE TRIMESTER DAN IMUNISASI ANAK - M. Putra Halomoan Daulay; Triase (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
This research aims to discuss information systems for monitoring the health of pregnant women in the 3 phases of trimesters and child immunization. In the city of Padangsidempuan, the high mortality rate in pregnant women and stunting in children is mostly due to the lack of concern for mothers to routinely carry out health monitoring and immunization for their children at the puskesmas. Some of them only came for the first monitoring and did not come again for the next visit. Apart from that, the puskesmas also still uses ledgers as a place to record monitoring results and data on every pregnant woman and child whose immunizations are considered to be less effective. So a monitoring information system is needed to assist the puskesmas in processing patient data and monitoring results and providing notifications to remind each mother for the next monitoring visit.